Design of a Web-Based E-Library Using the Model-View-Controller (MVC) Architecture for Aviation Vocational Education - Irfan; Sukarwoto; Qurina Ariantji P; Irwan Jaya; Putri Haifa R (Indonesian Journal of Multidisciplinary Scientific Studies, 2026)
The governance of instructional documents and specialized reference materials in aviation vocational education requires a repository system that ensures high data integrity, low access latency, and adaptive scalability. This study aims to design and develop a web-based electronic library (e-library) system specifically optimized for the Air Traffic Management Study Program. To overcome the limitations of conventional monolithic architectures, which are prone to data redundancy and integrity issues, the proposed system was developed using the System Development Life Cycle (SDLC) with the sequential linear (Waterfall) model and implemented through the Model–View–Controller (MVC) architectural pattern using the Laravel framework. The relational database environment was managed using MySQL Server with optimized implementation of Data Definition Language (DDL) and Data Manipulation Language (DML). The functional quality and system behavior were comprehensively evaluated using the Black Box Testing method with an equivalence partitioning approach. The results demonstrate that restructuring the database into an MVC-based e-library platform not only eliminates the risk of physical document loss and unauthorized manipulation of instructional data but also significantly reduces the time required to retrieve Air Traffic Control (ATC) reference materials through automated digital document indexing. Functional testing confirmed that all file management modules (add, edit, and delete) as well as user authentication functions achieved a 100% success rate. These findings indicate that the proposed system serves as a robust foundation for supporting digital academic knowledge management in higher vocational education.